ANALISIS KELELAHAN KERJA PADA PEKERJA BAGIAN PACKING DI PT. XYZ DENGAN METODE INDUSTRIAL FATIGUE RESEARCH COMMITTEE (IFRC) - Azri Rahmat Maklim Nasution; Nabila Yudisha; Margie Subahagia Ningsih; Rahmad Rezeki (Journal of Innovation Research and Knowledge, 2026)
PT. XYZ Tbk Medan Branch is a manufacturing company that produces instant noodles. This company is located in Tanjung Morawa, Deli Serdang Regency, North Sumatra. In facing competition in the current era of globalization, one of the efforts made by this company is to maintain the quality of the products produced so that they remain the main choice of consumers, from LKI data, the most frequent consumer complaints are in the packing section, namely 61.42%. This study aims to analyze worker fatigue at PT. XYZ in the packing section. The number of workers used as samples was 30 workers in the packing section, consisting of 6 seasoning checkers, 6 noodle sorters, 3 operators, 3 assistant operators, and 12 helper packers. Subjective work fatigue analysis used the Industrial Fatigue Research Committee (IFRC) questionnaire method and workload measurements were carried out which were calculated based on the 10 pulse method. Work fatigue in the production area was light 10%, moderate 63.33% and heavy 26.67%. ​The Pearson correlation values for workload, age, gender, and years of service are 0.893 (very strong), 0.737 (strong), 0.436 (moderate), and 0.363 (low), respectively. The results of the multiple regression analysis indicate that workload is the most influential factor on work fatigue, with a tstatistic value of 6.389.